Combined transcranial direct current stimulation and home-based occupational therapy for upper limb motor impairment following intracerebral hemorrhage: a double-blind randomized controlled trial. Issue 7 (26th March 2016) - Mortensen, Jesper; Figlewski, Krystian; Andersen, Henning
Abstract: Purpose : To investigate the combined effect of transcranial direct current stimulation (tDCS) and home-based occupational therapy on activities of daily living (ADL) and grip strength, in patients with upper limb motor impairment following intracerebral hemorrhage (ICH). Methods : A double-blind randomized controlled trial with one-week follow-up. Patients received five consecutive days of occupational therapy at home, combined with either anodal ( n = 8) or sham ( n = 7) tDCS. The primary outcome was ADL performance, which was assessed with the Jebsen–Taylor test (JTT). Results : Both groups improved JTT over time ( p < 0.01). The anodal group improved grip strength compared with the sham group from baseline to post-assessment ( p = 0.025). However, this difference was attenuated at one-week follow-up. There was a non-significant tendency for greater improvement in JTT in the anodal group compared with the sham group, from baseline to post-assessment ( p = 0.158). Conclusions : Five consecutive days of tDCS combined with occupational therapy provided greater improvements in grip strength compared with occupational therapy alone. tDCS is a promising add-on intervention regarding training of upper limb motor impairment. It is well tolerated by patients and can easily be applied for home-based training. Larger studies with long-term follow-up are needed to further explore possible effects of tDCS in patients with ICH. Implications for Rehabilitation: Five consecutive days of tDCS combined with occupational therapy provided greater improvements in grip strength compared with occupational therapy alone. tDCS is well tolerated by patients and can easily be applied for home-based rehabilitation.